Postgraduate Students’ Attitudes Toward Using E-learning at the Faculty of Physical Education and Sports Sciences: A Field Study at the University of Tripoli - Abdulmunem Saed Ahmed (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
The study aimed to identify the attitudes of postgraduate students (Master’s level) toward using e-learning at the Faculty of Physical Education and Sports Sciences, University of Tripoli. The researcher utilized a descriptive analytical approach to suit the nature of the research. The study population consisted of 30 Master’s students, and the research sample was selected randomly from this population. Data were collected using a questionnaire designed by the researcher, comprising 30 items distributed across three main dimensions: cognitive, affective, and behavioral. Results indicated that postgraduate students’ attitudes toward using e-learning were generally positive, with the overall mean ranging from moderate to high. The cognitive dimension ranked first, reflecting students’ awareness of the importance of e-learning in supporting self-learning, followed by the affective dimension in second place. The behavioral dimension ranked last, indicating some practical difficulties in the actual application of e-learning. Furthermore, the findings revealed statistically significant differences in favor of students possessing good technical skills, emphasizing the critical role of training and digital skill development in fostering positive attitudes. Based on these results, the study recommends enhancing technical training programs for postgraduate students and developing the technical infrastructure in higher education institutions to achieve the maximum benefit from e-learning.